PENGARUH KECEMASAN BELAJAR MATEMATIKA, PERSEPSI SISWA TENTANG KETERAMPILAN MENGAJAR GURU, DAN IKLIM KELAS TERHADAP HASIL BELAJAR MATEMATIKA MELALUI MOTIVASI BELAJAR PADA SISWA KELAS VIII SMP NEGERI DI TANA TORAJA - Suarti Djafar (Edumaspul: Jurnal Pendidikan, 2018)
The study aims at investigating the description and the influence of learning anxiety, students’ perceptions on teacher’s teaching skills, classroom climate, and learning motivation on learning outcomes of Mathematics. The study is an ex post facto with causality. The sample were 239 students of class VIII selected by employing proportional stratified random sampling. Data were collected using several instruments : (1) questionnaire of learning anxiety, (2) questionnaire of students’ perception on teacher’s teaching skills, (3) questionnaire of classroom climate, (4) questionnaire of learning motivation, and (5) test of learning outcomes. Data were analyzed using descriptive statistics and inferential statistics with SEM method. The results of the study reveal that (1) class VIII students at SMP in Tana Toraja have medium learning anxiety, students’ perception on teacher’s teaching skills is in high category, the classroom climate is in high category, learning motivation is in high category, and learning outcomes is in medium category, (2) the learning anxiety gives positive and significant influence (p = 0,379) on learning outcomes, (3) students’ perception on teacher’s teaching skills give positive and significant influence (p = 0,473) on learning outcomes, (4) classroom climate gives negative and significant influence (p=0,519) on learning outcomes, (5) learning anxiety gives positive but insignificant (p=0,9317) on learning outcomes through learning motivation, (6) students’ perception on teacher’s teaching skills give positive and significant influence (p=0,9447) on learning outcomes through learning motivation of students, (7) classroom climate gives negative and insignificant influence ((p=0,9015) on learning outcomes through learning motivation of students.